Integration of Industry 4.0 and 5.0: Optimizing Sustainable Processes in Industrial Engineering - Acuña Acuña, Edwin Gerardo (LACCEI, 2025)
The integration of advanced automation from Industry 4.0 with the human-centered sustainability of Industry 5.0 marks a critical shift in modern industrial engineering. This research delves into how cognitive digital clones can enable the convergence of these two paradigms, enhancing both operational efficiency and decision-making processes in a more sustainable, human-oriented way. A mixed-methods approach was applied, including a thorough review of relevant literature and an analysis of case studies from companies already adopting these technologies. Quantitative data showed a 20% increase in operational efficiency and a 15% reduction in carbon emissions, underscoring the positive impact of this integration. Additionally, qualitative interviews revealed that human involvement in decision-making significantly improves organizational resilience in the face of unexpected disruptions. These findings suggest that this technological hybridization not only boosts productivity but also fosters more sustainable and adaptable industrial practices, which are essential in addressing global challenges such as climate change and economic instability. In conclusion, effective collaboration between humans and machines, supported by advanced cognitive technologies, offers a key strategy for the future of industrial engineering, allowing companies to remain competitive and sustainable in an increasingly demanding global landscape.